Fiscal policy formulation and implementation in oil-producing countries - Ossowski, Rolando; Davis, Jeffrey M., 1946-; Fedelino, Annalisa; International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This book brings together studies that provide analysis and findings on fiscal policy issues in oil-producing countries from a diverse international perspective. A key focus for the authors is how to manage oil resources in a way that contributes to a stable macroeconomic environment, sustainable growth, and poverty reduction.
Includes bibliographical references.
oif 20/08/15
Loan
Keywords: Petroleum products -- Prices; Fiscal policy; Petroleum -- Taxation; Petroleum industry and trade